2022
DOI: 10.3389/fonc.2022.978069
|View full text |Cite
|
Sign up to set email alerts
|

Liver metastases and the efficacy of immune checkpoint inhibitors in advanced lung cancer: A systematic review and meta-analysis

Abstract: BackgroundLiver metastasis is the most common type of lung cancer metastasis, and is a significant prognostic factor in lung cancer. However, the effect of liver metastases on the efficacy of immune checkpoint inhibitors (ICIs) remains inconsistent and controversial. The aim of this study was to explore the relationship between liver metastases and ICI efficacy in patients with advanced lung cancer based on data from randomized controlled trials (RCTs) and observational studies.MethodsPubMed, EMBASE, Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“… 40 These are consistent with our findings, again suggesting that treatment combination options are one of the factors affecting the efficacy of immunotherapy. Additional studies 41 , 42 also assessed the relationship between liver metastasis and efficacy of immunotherapy. While these 2 studies were focusing on both NSCLC and small cell lung cancer, we only included and analyzed the data from RCTs conducted in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“… 40 These are consistent with our findings, again suggesting that treatment combination options are one of the factors affecting the efficacy of immunotherapy. Additional studies 41 , 42 also assessed the relationship between liver metastasis and efficacy of immunotherapy. While these 2 studies were focusing on both NSCLC and small cell lung cancer, we only included and analyzed the data from RCTs conducted in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The response rates still exceeded those reported for other therapies, although the efficacy was worse than those without LMs. That meta-analysis of 12 RCTS [ 16 ] also showed that ICIs therapy (ICIs monotherapy, ICIs combined therapy) had a survival advantage in patients with LMs compared to standard therapy (PFS HR, 0.77; 95%CI, 0.61–0.97; OS HR, 0.78; 95%CI, 0.68–0.90). In a real-world retrospective study [ 21 ] of 1470 advanced NSCLC patients, 234 (15.9%) developed LMs at initial diagnosis.…”
Section: Introductionmentioning
confidence: 97%
“…Some studies have identified LMs as an independent poor prognostic factor in patients who received ICIs [ 3 , 15 , 16 ]. In a retrospective study receiving pembrolizumab for NSCLC, Tumeh et al discovered that NSCLC patients with LMs had a significantly shorter progression-free survival (PFS) (1.8 vs. 4.0 months, p = 0.0094) and lower objective response rate (ORR) (28.6 vs. 56.7%) than patients with non-liver metastasis, and they confirmed that LMs was predictive of reduced response and poor outcome independently [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations